2017
DOI: 10.1155/2017/5083463
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Negative Monomorphic B-Cell Posttransplant Lymphoproliferative Disorder with Marked Morphologic Pleomorphism and Pathogenic Mutations in ASXL1, BCOR, CDKN2A, NF1, and TP53

Abstract: Posttransplant lymphoproliferative disorders (PTLDs) are a diverse group of lymphoid or plasmacytic proliferations frequently driven by Epstein-Barr virus (EBV). EBV-negative PTLDs appear to represent a distinct entity. This report describes an unusual case of a 33-year-old woman that developed a monomorphic EBV-negative PTLD consistent with diffuse large B-cell lymphoma (DLBCL) 13 years after heart-lung transplant. Histological examination revealed marked pleomorphism of the malignant cells including nodular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Although the translocations or deletions of ETV6 gene are reported in a variety of hematologic neoplasms, including acute myeloid and lymphoblastic leukemia, myelodysplastic syndrome, and myeloproliferative disorders, it is rarely reported in DLBCL [ 34 , 35 ]. A mutational analysis of primary central nervous system lymphoma also revealed that ETV6 might be an underlying target for this kind of lymphoma treatment [ 36 ]. In recent study [ 37 ], ETV6 and other 149 genes are identified as driver genes of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Although the translocations or deletions of ETV6 gene are reported in a variety of hematologic neoplasms, including acute myeloid and lymphoblastic leukemia, myelodysplastic syndrome, and myeloproliferative disorders, it is rarely reported in DLBCL [ 34 , 35 ]. A mutational analysis of primary central nervous system lymphoma also revealed that ETV6 might be an underlying target for this kind of lymphoma treatment [ 36 ]. In recent study [ 37 ], ETV6 and other 149 genes are identified as driver genes of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive molecular studies were performed on a monomorphic EBV-negative PTLD case that developed 13 years after a combined heart-lung transplant and revealed genetic alterations including 6 pathogenic mutations ( ASXL1 , BCOR , CDKN2A , NF1 , and TP53 x2) and 30 variants of unknown significance. 4 A study of 32 cases of monomorphic PTLD from two institutions also found that PTLDs diagnosed in the small bowel/mesentery were statistically more likely to be EBV-negative by EBER in situ hybridization, and they more frequently contained a pathogenic TP53 mutation than PTLDs diagnosed at other locations. All the EBV-negative cases subjected to testing (9 of 9, mostly adults) carried TP53 mutations, while only 2 of 15 EBV-positive cases showed mutated TP53.…”
Section: Discussionmentioning
confidence: 96%
“…Earlyonset PTLDs are typically EBV-driven lymphoproliferations, whereas late onset patients typically have monoclonal lymphoid malignancies that can lack EBV association. 4 The median time to developing PTLD is on average only 16 months for EBV-positive cases, whereas EBV-negative cases often develop PTLD much later (median time of 102 months after transplant). 5 In recent years, we also gained more knowledge about the pathologic characteristics of different forms of monomorphic B-cell PTLDs, and these differences may reflect the variations in pathogenesis of EBV-negative and positive cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What was rather unexpected were also findings regarding ETV6, which is an ETS family transcriptional factor with a crucial role in hematopoiesis and embryonic development [ 50 ]. While ETV6 is frequently rearranged or fused with other genes in human myeloid and lymphoid leukemias [ 51 , 52 ], it is only rarely altered in B-cell lymphoma [ 53 , 54 ]. Recently, however, whole-exome sequencing studies have found a significant fraction of DLBCL samples (mainly of the ABC-subtype) harboring ETV6 mutations/alterations [ 35 , 55 ].…”
Section: Discussionmentioning
confidence: 99%